Metallosis After Swanson Spacer as Indication for Volar Synovectomy 12 Years After Implantation - Trieb, Klemens (Current Rheumatology Reviews, 2017)
The treatment of metacarpophalangeal destruction by rheumatoid arthritis is an indication for arthroplasty, the swanson spacer is one of the options. The flexible silicone spacer may be implanted with or without titanium guide sleeves (
Keywords: Metacarpophalangeal